Answer:
A. -4
Step-by-step explanation:
F(-1) means we must plug the number "-1" in for each x.
F(x) = x^2 + 3x - 2
F(-1) = (-1)^2 + 3(-1) - 2
= 1 - 3 - 2
= -4
<span>7,004,000 in scientific notation.
=</span>7.004 x 10^6
as 7 is the first non zero digit
so decimal jumbed 6 numbers from right to left and exponent will be positive
option A is correct
hopr this helps
Answer:
14.97
Step-by-step explanation:
Answer:
y-7=4x(x+3)
Step-by-step explanation:
(The 4x is 4 times ...)
Answer:
.83 cents
Step-by-step explanation: